Partisipasi masyarakat dalam pengelolaan sampah pemukiman di Kecamatan Senapelan Kota Pekanbaru - Febriana Zulmi; Yusni Ikhwan Siregar; Thamrin Thamrin (Pelantar Press, 2022)
The problem of waste management which is still a city problem, if the waste is not done properly it will cause problems. Uncontrolled piles of garbage due to human activities will have an impact on environmental problems such as decreasing the beauty of the city, the emergence of odors from waste decomposition, the occurrence of air pollution due to burning waste that interferes with public health and a source of disease for human health. This research was conducted in Senapelan District, Pekanbaru City from February to April 2022. The type of research is quantitative analytic with cross sectional. The population is all heads of families with a sample of 94 people with purposive sampling. The results showed that there was no influence of age, education, occupation, on community participation in residential waste management in Senapelan District, Pekanbaru City and there was an influence on infrastructure, knowledge, perception, on community participation in residential waste management in Senapelan District, Pekanbaru City. It takes a conducive environment and good infrastructure in waste management in settlements in Senapelan District, Pekanbaru City